Legal and administrative framework on the enforcement of Shari'ah penal law by the police in Nigeria - Okemuyiwa, Adedeji Akeem (Ahmad Ibrahim Kulliyyah of Laws, International Islamic University Malaysia, 2016)
Nigeria is a Federal state with a central Federal Government and 36 federating units, each of which is constitutionally empowered to make laws subject to the extent permitted by the constitution. In line with the powers conferred on them about 12 States in Northern part of Nigeria about a decade ago enacted legislations introducing Shari'ah Penal Laws into their domains. Meanwhile Shari'ah Law is a residual matter for States while the Police that enforce all laws is a federal agency. The enforcement of the Shari'ah Penal System is therefore bound to face some legal and administrative challenges. This research as such seeks to justify the introduction of Shari'ah Penal Law in Nigeria and argues that the Police as an institution must take responsibility for the enforcement of Shari'ah penal law. In furtherance of the above, this research analyses the Constitution of the Federal Republic of Nigeria, the Police Act and all relevant laws. In appropriate cases, references have been made into literature on law and Policing, not forgetting observations and experience of the researcher as a serving Police Officer. This research finds that the Nigeria Police shoulder a lot of responsibility in the enforcement of all laws in Nigeria including Shari'ah but is dwarfed by gargantuan legal and administrative problems which are both internal and external to it. Another critical finding of our study is that a centralized police in a Federal State like Nigeria limits the power of the federating units to enforce their own laws. Unfortunately our study has shown that multiple policing is a remote possibility in Nigeria. Accordingly devolution of powers to State Police Commands has been recommended as a practicable solution to lift the police.